Implementasi Pembelajaran Kreativitas Inovasi dan Kewirausahaan untuk Membentuk Jiwa Wirausaha Murid di SMKN 1 Karangtengah Cianjur - Ratna Wulan Munggarini; Khaerul Syobar; Ernandika Pandikar (EDUKASI, 2026)
This study examines the implementation of creativity, innovation, and entrepreneurship (KIK) learning in shaping students’ entrepreneurial mindset at SMKN 1 Karangtengah, Cianjur. Using a qualitative case study approach within a social constructivist paradigm, the research explores how project-based learning (PjBL) is planned, implemented, and evaluated in the KIK subject. Data were collected through observation, in-depth interviews, documentation, and focus group discussions involving the principal, teachers, and students. The findings reveal that KIK learning has been implemented through short-term PjBL that provides meaningful and contextual learning experiences. Students actively engage in designing business ideas, producing products, collaborating in teams, and presenting their work. This process fosters social-pedagogical dynamics that strengthen collaboration, responsibility, communication skills, and risk-taking behavior. However, several challenges remain, particularly in project marketing planning and evaluation systems that still emphasize final products rather than the development of entrepreneurial character. Supporting factors include the merdeka curriculum policy, active teacher facilitation, the presence of a student business center, and partnerships with local industries. In contrast, limitations in capital, infrastructure, time allocation, and students’ marketing experience act as inhibiting factors. The study concludes that KIK learning based on PjBL significantly contributes to the formation of students’ entrepreneurial character through authentic learning experiences. Strengthening planning and evaluation strategies is essential to optimize entrepreneurship education in vocational schools.